Predicting Response to Omalizumab in Chronic Urticaria Based on Biomarkers - Misbah Noshela Ghazanfar; Simon Francis Thomsen (European Medical Journal, 2018)
Chronic urticaria (CU) is characterised by intense recurrent itch, wheals, and/or angioedema, persisting for >6 weeks. CU can be subdivided into chronic spontaneous urticaria and chronic inducible urticaria; the latter usually appears with physical stimuli, such as heat, cold, pressure, and sunlight. The recommended treatment for CU is non-sedating oral antihistamines, administered up to four times a day. The monoclonal antibody omalizumab (anti-IgE) is recommended as an add-on therapy for patients with antihistamine-refractory CU. The fluctuating nature of urticaria symptoms and varying response to omalizumab often makes it difficult to predict the response to omalizumab; this often leads to individualised dosage regimens for CU patients. However, being able to predict the response to omalizumab treatment would lead to an improvement in dosage regimens and treatment plans in the clinical setting. Several studies have investigated potential CU biomarkers; however, no reliable biomarkers have been discovered that can be used to assess the treatment response to omalizumab in the clinic. Some potential biomarkers, such as plasma D-dimer, serum total IgE levels, the basophil histamine release assay, the autologous serum skin test, and the basophil activation test, have been suggested for predicting disease activity and response to omalizumab but are not implemented routinely in clinical practice. This paper presents an overview of the various biomarkers associated with response to omalizumab in CU.